Effects of training on the execution of complete-arch scans: Part 2: scanning accuracy - Waldecker, Moritz; Rues, Stefan; Trebing, Charlotte Theresa; Behnisch, Rouven; Rammelsberg, Peter; Bömicke, Wolfgang (The international journal of prosthodontics, 2021)
Moritz Waldecker, Dr Med Dent/Stefan Rues, Dipl-Ing/Charlotte Trebing, Dr Med Dent/Rouven Behnisch, MSc/Peter Rammelsberg, Prof Dr Med Dent/Wolfgang Bömicke, PD Dr Med Dent, MSc: Purpose: To investigate the effect of training on scanning accuracy of complete arch scans (CAS) performed - by first-time users, with a distinction made between specific training (repeated performance of CAS) and - nonspecific training (simple use of an intraoral optical scanner for a sextant scan in the context of a CAD/CAM teaching module). Materials and Methods: A total of 36 students with no experience in intraoral - scanning were randomized into three groups (n = 12 per group) according to the number of CAS sessions: - three sessions (3S), two sessions (2S), and one session (1S). Each student had to perform 10 CAS per scanning - session. Sessions were scheduled at T0, T1, and T2 for group 3S; at T0 and T2 for group 2S; and at T2 for - group 1S. Before the final scanning session in each group (ie, the first scanning session in group 1S), the - students completed a CAD/CAM teaching module, which included fabrication of a monolithic crown in a - fully digital chairside workflow. Results: In all groups, repeated CAS resulted in improved scanning accuracy. - Participation in the CAD/CAM module had a positive effect on initial accuracy for CAS. Mean absolute - deviations in cross-arch distance were 84 μm (T0), 68 μm (T1), and 63 μm (T2) for group 3S; 79 μm (T0) and - 61 μm (T2) for group 2S; and 67 μm (T2) for group 1S. Conclusion: To perform CAS with the best possible - accuracy, specific training is highly recommended. In addition, nonspecific training leads to an improvement - in initial scanning accuracy.
Gesehen am 10.09.2021